2015
DOI: 10.1115/1.4029519
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Function- and Affordance-Based Design Representations

Abstract: In this paper, we explore the possibility of reconciling and integrating practical affordance- and function-based design representations. We present a classic function-based design method and representation and argue for the benefits of augmenting it with affordance-based approaches. Building on existing function concept ontologies, we present an integrated approach to developing early-stage design representations. This approach combines the use of affordance and function representations to capture user needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Quality tells us how well a system affords a specific use or action, in this case, based on the perception of the user. This definition of quality has been embraced by other authors (Cormier, Olewnik & Lewis 2014;Ciavola, Wu & Gershenson 2015;Ben Hamida et al 2016). Products often go through many iterations (e.g., vacuum cleaners, cars, power tools), and it can be assumed that their quality increases in every iteration.…”
Section: Product Evolution By Improving Affordancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality tells us how well a system affords a specific use or action, in this case, based on the perception of the user. This definition of quality has been embraced by other authors (Cormier, Olewnik & Lewis 2014;Ciavola, Wu & Gershenson 2015;Ben Hamida et al 2016). Products often go through many iterations (e.g., vacuum cleaners, cars, power tools), and it can be assumed that their quality increases in every iteration.…”
Section: Product Evolution By Improving Affordancesmentioning
confidence: 99%
“…With an appropriate interface, users could suggest that an affordance be added to the product. Ciavola et al (2015) found a way to integrate the concept of affordances with genetic algorithms (GAs) and make some physical characteristics of objects change according to the evaluation of the quality of their affordances. However, their research did not make use of real end users; instead, they implemented a neural network that was trained by one user and mimicked input from that user.…”
Section: Product Evolution By Improving Affordancesmentioning
confidence: 99%
“…Future work is needed to integrate them [29]. Ciavola [30] initiates a framework to use in conjunction functions and affordances, linking high-level affordance information with low-level function information.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Blessing (2005) connect affordance to function (also see Vermaas, 2009; Ciavola et al, 2015, for extensions to that analysis). Brown and Blessing point out that when an artifact provides a function to a user, it has a set of interactions or relationships with the environment (where the environment includes the user) so that those interactions play a desired role for the user.…”
Section: Introductionmentioning
confidence: 99%